Sensory perception and pleasantness of orange beverages from childhood to old age - Zandstra, Elizabeth H.; de Graaf, Cees (Food quality and preference, 1998)
Sensory perception and pleasantness of orange beverages were investigated in 31 children (6–12 years); 30 adolescents (13–18 years); 30 young adults (19–34 years); 30 adults (35–49 years); 29 older adults (50–65 years) and 30 elderly subjects (65 + years). The beverages varied in sucrose (8.24–23.53 % w w ), citric acid (0.180–0.911 % 0 aq w w ) and orange flavour (40–320 ppm) concentrations. Subjects rated the pleasantness, perceived sweetness intensity, sourness intensity and orange flavour intensity on a 5-point category scale. Results showed that children and elderly subjects were less sensitive to the sweetness of sucrose, and had higher optimal sucrose concentrations than young adults. The aversion to high citric acid concentrations decreased with increasing age, and was accompanied by a lower slope of the psychophysical function of citric acid. The slopes of the psychophysical functions of orange flavour were not significantly different for the age groups. There was a trend that the optimal preferred concentrations were higher for the elderly subjects than for the other age groups with the exception of the children who also preferred higher optimal concentrations of sucrose and orange flavour.